1971
DOI: 10.1017/s0031182000079580
|View full text |Cite
|
Sign up to set email alerts
|

Changes in adult Nippostrongylus brasiliensis during the development of immunity to this nematode in rats: 2. Total lipids and neutral lipids

Abstract: SUMMARYThe total lipids and the amount of neutral lipids of male and female N. brasiliensis, from 7-day and 15-day infections, have been studied quantitatively. There is an increase in total lipids from 10·9 ± 2 to 15·5 ± 2 % in females and an increase from 8·4 ± 1 to 14·6 ± 2 % in males. In both sexes there is a rise in cholesterol and trigylceride content and a fall in free fatty acid content. These changes are discussed with reference to the development of immunity of the host to this nematode.I wish to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In this case, antiacetylcholinesterase antibodies might act by interfering with this 'holdfast' function forcing the worms to leave their position of choice in intimate con- tact with the mucosa and migrate towards the gut lumen. The occurrence of lipid droplets and an accumulation of neutral lipid in antibody damaged worms (Lee 1971) supports the hypothesis that antibodies make the worms move into an environment where the oxygen potential is unfavourable to them. Nevertheless, this is not enough to cause their expulsion, which requires the further action of cells.…”
Section: The Immunoglobulin Response and Its Effect On The Parasitesupporting
confidence: 58%
“…In this case, antiacetylcholinesterase antibodies might act by interfering with this 'holdfast' function forcing the worms to leave their position of choice in intimate con- tact with the mucosa and migrate towards the gut lumen. The occurrence of lipid droplets and an accumulation of neutral lipid in antibody damaged worms (Lee 1971) supports the hypothesis that antibodies make the worms move into an environment where the oxygen potential is unfavourable to them. Nevertheless, this is not enough to cause their expulsion, which requires the further action of cells.…”
Section: The Immunoglobulin Response and Its Effect On The Parasitesupporting
confidence: 58%
“…Ultrastructural examination of the gut cells of worms, taken from rats with primary infections of differing duration, showed the progressive replacement of ribosomes by large vacuoles. Lee described, in addition to intestinal changes, the appearance of large droplets, probably lipid in nature (Lee, 1969(Lee, , 1971, in the cytoplasm of the hypodermis, excretory glands, muscle and reproductive system. Ogilvie & Jones (1971), in a review of N. brasiliensis and the host/parasite relationship, suggested that since it was improbable that these changes were unique to this parasite, it would be of interest to discover if similar changes occurred in other nematodes affected by immunity.…”
Section: Introductionmentioning
confidence: 99%
“…TG constituted major lipids (80.9% of total 327 lipids) identified from the somatic extract of the L3 stage of H. contortus and it decreases as they mature into L4 stage [119]. Lee [125] also reported triglycerides as a major lipid constituent in the adult tissue of N. brasiliensis, which was presumed to be due to reduced lipid metabolism under anaerobic conditions inside their host. Triglyceride is the major neutral lipid in the majority of helminths [126].…”
Section: Discussionmentioning
confidence: 96%